2002
DOI: 10.1055/s-2002-25342
|View full text |Cite
|
Sign up to set email alerts
|

Directed Deprotonation-Transmetallation of 4-Bromopyridine: Flexible Routes to Substituted Pyridines

Abstract: Halide-directed deprotonation and Li-Zn exchange of 4-bromopyridine 4 provides organozinc 6, which undergoes Pdmediated coupling to give the 3-aryl-4-bromopyridines 7. Further substitution is achieved to provide the 3,4-disubstituted pyridines 8 and 9, and the 3,4,5-trisubstituted variants 10.We 1 recently described an entry to ring substituted pyridines based on a sequence involving (i) the halidedirected deprotonation (ii) transmetallation to generate a pyridyl organozinc and (iii) Pd(0)-mediated Negishi cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Compound 48 represents a class of pyridines with nonidentical diaryl substitution for which only two synthetic methods are available. 55 …”
Section: Resultsmentioning
confidence: 99%
“…Compound 48 represents a class of pyridines with nonidentical diaryl substitution for which only two synthetic methods are available. 55 …”
Section: Resultsmentioning
confidence: 99%
“…16 The anionic thia-Fries rearrangement proceeds under markedly different conditions (low temperature basic medium) and undoubtedly proceeds via a different mechanism, giving only the ortho-rearranged product. Furthermore, the two processes can be regio-complementary, for example 2-naphthyl triflate (8) gives the 3-sulfonyl isomer (10) whereas under the microwave/ acidic conditions, 2-naphthyl tosylate (11) gives the 1-sulfonyl isomer (12), Scheme 4. 16 In stark contrast to anionic conditions (Table 1 entry 3), o-chlorophenyl triflate (5) fails to rearrange on heating (oil bath or microwave) neat, in solution (Table 1, entry 5) or on a Lewis acidic support ** In summary, aryl triflates bearing moderately electron withdrawing substituents, especially at an ortho-position, readily undergo an anionic thia-Fries rearrangement on reaction with LDA in the presence of THF to give o-hydroxyaryl trifluoromethylsulfones rather than generating arynes.…”
Section: T H I S J O U R N a L I S © T H E R O Y A L S O C I E T Y O Fmentioning
confidence: 99%
“…4,7 We recently attempted a Pd-catalysed cross-coupling of 1-chloro-2-naphthalene triflate 1 9 with a pyridyl zinc halide, generated in situ using LDA/ZnCl 2 . 10 A side product of the reaction was ultimately identified as 2, the product of a thia-Fries rearrangement of 1. Further experiments revealed that LDA mediates rearrangement and under simpler conditions (1.0 equiv.…”
mentioning
confidence: 99%
“…Recently, a number of groups have reported the directed lithiation and transmetalation of pyridines, combined with subsequent Pd(0)-mediated cross-coupling reactions to provide an entry to substituted pyridines. We utilized the regioselective C-4 deprotonation of 3-bromopyridine, followed by a Li/Zn transmetalation and Pd(0)-mediated Negishi coupling, to provide 3,4-disubstituted pyridines 4a. 2-Bromopyridine provides an entry to 2,3- and 2,4-disubstituted pyridines,4a and 3,4-disubstituted and 3,4,5-trisubstituted pyridines are available by application of directed ortho -lithiation procedures to 4-bromopyridine 4b.…”
mentioning
confidence: 99%
“…We utilized the regioselective C-4 deprotonation of 3-bromopyridine, followed by a Li/Zn transmetalation and Pd(0)-mediated Negishi coupling, to provide 3,4-disubstituted pyridines 4a. 2-Bromopyridine provides an entry to 2,3- and 2,4-disubstituted pyridines,4a and 3,4-disubstituted and 3,4,5-trisubstituted pyridines are available by application of directed ortho -lithiation procedures to 4-bromopyridine 4b. Rault and co-workers have described a series of other boronated halopyridines, including 2-halo-5-pyridyl, 2-, 4-, or 5-halo-3-pyridyl, and 2- or 3-halo-4-pyridyl boronic acids, which undergo efficient Suzuki coupling reactions .…”
mentioning
confidence: 99%